Grapevine rootstocks resistant to the root‐knot nematode Meloidogyne javanica. (25th July 2016) - Smith, B.P.; Morales, N.B.; Thomas, M.R.; Smith, H.M.; Clingeleffer, P.R.
Abstract: Background and Aims: Root‐knot nematodes ( Meloidogyne spp.) are endo‐parasites of plant roots and parasitisation can lead to diminished grape yields. Worldwide viticulture production is impacted primarily by four species of root‐knot nematode ( Meloidogyne arenaria, Meloidogyne hapla, Meloidogyne incognita and Meloidogyne javanica ). Meloidogyne javanica is the predominant root‐knot nematode found in Australian vineyards. A glasshouse‐based experiment was conducted to identify grapevine cultivars and accessions with complete resistance (i.e. no reproduction of nematode) to an aggressive pathotype of M .  javanica isolated from an Australian vineyard. Methods and Results: Single‐grapevine plants were inoculated with approximately 1500 second stage juveniles of M .  javanica in a replicated study. Six weeks after inoculation, roots were washed free of soil, and egg masses were stained and tallied. The final dry mass of roots was measured to determine the ratio of egg masses to root mass. Conclusions: Complete resistance to M .  javanica was found in 42 of 75 Vitis cultivars and accessions screened. Significance of Study: The M .  javanica resistant cultivars and accessions identified in this study provide valuable material for future breeding in order to develop new rootstocks for the Australian wine and grape industry with durable resistance to root‐knot nematode.